Testimony of Walter B. Wriston - Wriston, Walter B. (Tufts Archival Research Center, 2007)
The document was created from the speech, "Testimony of Walter B. Wriston," written by Walter B. Wriston for the Subcommittee on Oversight and Investigations of the Committee on Energy and Commerce House of Representatives on 28 June 1983. The original speech is located in MS134.001.005.00014.